Islamic Religious Education as a Foundation for Developing Ethical and Humanistic Character among Prospective Healthcare Professionals - Wiwik Widiyati (Al-Munawwarah: Journal of Islamic Education, 2026)
Islamic Religious Education plays an important role in preparing prospective healthcare professionals who are not only technically competent but also ethically responsible and humanistically oriented. This study analyses Islamic Religious Education as a foundation for developing ethical and humanistic character among prospective healthcare professionals. It employed qualitative library research with a structured narrative review approach. Forty-five scholarly publications were examined through qualitative content analysis, including repeated reading, coding, thematic categorisation, and conceptual synthesis. The findings indicate that Islamic Religious Education strengthens ethical character through the internalisation of honesty, trustworthiness, justice, responsibility, excellence, and moral accountability. It also supports humanistic character by cultivating empathy, compassion, respectful communication, patient-centred care, and recognition of human dignity. The integration of Islamic ethics, maqāṣid al-sharī‘ah, and health sciences provides a moral framework for addressing professional and bioethical challenges. However, religious knowledge does not automatically produce ethical behaviour; effective character formation requires contextual learning, clinical cases, reflection, mentoring, role modelling, habituation, interdisciplinary curriculum integration, and competency-based assessment. This study concludes that Islamic Religious Education should be positioned as an integral component of health professions education rather than merely a compulsory general course. Its integration can support the formation of healthcare professionals who combine scientific competence, ethical integrity, spiritual awareness, and compassionate service.